The unmet needs of palliative care among patients with non-malignant chronic illness in Indonesia: A phenomenology study - Merduaty, Rona Cahyantari; Nuraini, Tuti; Sihwastuti, Sihwastuti (Faculty of Nursing Universitas Padjadjaran, 2024)
Background and Objectives: People with chronic illness tend to report multiple and complex symptoms that decrease their ability to meet their needs and quality of life (QoL). As an approach to address people with chronic illness, palliative care is still shortly focused on people with chronic malignancies in Indonesia. Eventually, that paradigm makes the spectrum of palliative care interpreted narrowly only for cancer or end-of-life (EOL) patients. This study explores the experience and needs of patients diagnosed with non-malignant chronic illness towards their illness to identify the need for palliative care. This study used a qualitative method with a phenomenological approach. Material and Methods: A total of seven (7) participants were involved in semi-structured interviews that were previously selected based on screening using an adult palliative patient score developed by Cipto Mangunkusumo Hospital (RSCM), Jakarta. Only participants with a score above or equal to 4 (four) are selected to participate. All qualitative data is recorded, transcribed, and analyzed using Colaizzi's approach. Results: There are seven major interrelated themes emerging from this qualitative study that uniquely match with the illness trajectory of non-malignant chronic patients. The themes are: (1) negative feelings that cannot be described at the time of diagnosis, (2) ignorance of the disease process, (3) late realization that illness cannot be cured, (4) helplessness during the medication/treatment process, (5) shame of being a burden to family and surroundings, (6) limited access, (7) family and God as motivation and hope reinforcement to recover at the end of illness stage. Conclusions: People with non-malignant chronic complain of several challenges, which are not much different from those with cancer. Therefore, patients with non-malignant chronic illness (PWNMCI) also have a similar need for palliative care. A deeper and broader assessment of palliative care should also be implemented in patients with non-malignant chronic illness from the early diagnostic process.